Vitamin D Insufficiency/Deficiency in Patients on a Community Psychiatric Rehabilitation Unit - Saeed Yahya, Dr Ahmed Saeed Yahya (International Journal of Psychosocial Rehabilitation, 2017)
Vitamin D deficiency is known to have mental health consequences. There is evidence that Vitamin D deficiency/insufficiency is prevalent amongst patients with severe and enduring mental illness. In spite of this Vitamin D screening is not routinely indicated as a screening measure in psychiatric rehabilitation units in the United Kingdom. We tested the total Vitamin D serum levels in 13 out of 14 patients in a UK-based Community Psychiatric Rehabilitation unit. The objective was to quantify the prevalence of vitamin D deficiency/insufficiency in this setting and to make recommendations that could be used in clinical practice. Four of the thirteen patients were already on Vitamin D replacement therapy. Eight out of the nine patients (89%) who were not on replacement therapy were found to have insufficient or deficient levels of Vitamin D (levels of 50nmol/L or less). These results suggest that the routine screening of total serum Vitamin D levels in psychiatric rehabilitation units should be implemented. Organisations providing care to this at-risk patient group might also want to consider providing low dose Vitamin D replacement therapy in Psychiatric Rehabilitation units.